Serum Anti Mullerian Hormone level as ovarium response predictor at women received ovarium stimulation invitro - Soebijanto, Soegiharto (Indonesian Socety of Obstetrics and Gynecology, 2009)
Objective: To evaluate clinical value of basal anti-Mullerian Hormone level as predictor of ovarian response to stimulation in women following in vitro fertilization program; compared with Follicle Stimulating Hormone (FSH), estradiol and basal antral follicle. Method: Research was conducted in Yasmin Clinic Cipto Mangunkusumo Hospital as tertiary referral center for reproductive health and in vitro fertilization. Infertile patients which going to undergo controlled ovarian hyper stimulation cycle for in vitro fertilization were checked for basal FSH level, estradiol level, AMH level and amount of basal antral follicle. We were divided the sample into two categories; poor responders and good responders. Statistical analysis using ANOVA was done to evaluate demographic data and Receiver Operator Characteristic area under curve (ROCAUC), and to analyze whether AMH was more superior than the other 3 predictors and to get the cut off point for AMH level. Result: We have collected 22 patients data; 14 were categorized as good responders and 8 were bad responders. Mean AMH value in the good responders group was 4.46Â±1,01 and in the poor responders group was 1,35Â±0,96, with p 0,000. According to ROCAUC, AMH is a good predictor for good ovarian response in patient who are a good responders (AUC 0,821), compared to the other three predictors (FSH, E2 and basal antral follicle). Anti Mullerian Hormone cut-off point level is 3, which means value